2002
DOI: 10.1021/jf011711z
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Method for Determining Antioxidant Distributions in Model Food Emulsions:  Distribution Constants of t-Butylhydroquinone in Mixtures of Octane, Water, and a Nonionic Emulsifier

Abstract: The absence of reliable estimates of distributions of antioxidants in food emulsions hinders the development of a useful method for comparing the efficiencies of antioxidants. Here we describe the application of a pseudophase kinetic model, originally developed for homogeneous microemulsions, to the determination of distribution constants of tert-butylhydroquinone, TBHQ, in a fluid, opaque, model food emulsion composed of the nonionic emulsifier C(12)E(6), octane, and water. This kinetic method should be appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 53 publications
(104 reference statements)
2
45
0
Order By: Relevance
“…Rates of reactions of arenediazonium ions with AOs are sensitive to both temperature and pH and both must be carefully controlled to obtain reliable data [13]. Emulsions of 1:1 and 1:4 volume ratios of octane to water were prepared in a beaker by mixing together with a magnetic stirrer bar 5 mL of octane, 5 mL of aqueous 3 mM HCl, and 2 mL of octane and 8 mL of aqueous 3 mM HCl, respectively, and a weighed amount of C 12 E 6 (assumed density = 1 g/mL).…”
Section: Preparation Of Emulsions Electrochemical Kinetics Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Rates of reactions of arenediazonium ions with AOs are sensitive to both temperature and pH and both must be carefully controlled to obtain reliable data [13]. Emulsions of 1:1 and 1:4 volume ratios of octane to water were prepared in a beaker by mixing together with a magnetic stirrer bar 5 mL of octane, 5 mL of aqueous 3 mM HCl, and 2 mL of octane and 8 mL of aqueous 3 mM HCl, respectively, and a weighed amount of C 12 E 6 (assumed density = 1 g/mL).…”
Section: Preparation Of Emulsions Electrochemical Kinetics Experimentsmentioning
confidence: 99%
“…The problem is complex because AO effectiveness depends on a number of properties of the system such as the substrates being oxidized, the distribution of the AO within the emulsion, and the presence of free radical initiators such as transition metals [1]. AOs and polar solutes distribute between the oil, interfacial and water regions of the emulsion [7,13], but little is known about the fraction of AO in each region.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, it is found that they are limited in study of biological samples, such as analyses of metabolites, which is very important to study the pharmacokinetics and toxicology of TBHQ. HPLC coupled with mass spectrometry is a currently developed unique technique for monitoring antioxidant content and studying compound structure [11]. In particular, MS/MS triple quadrupole mass spectrometry in the multiple reaction monitoring modes (MRM) provides surpassing speed, sensitivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%